2021
DOI: 10.4236/jpee.2021.98004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Performance, Exhaust Gas Temperature and Speed of a Spark Ignition Engine Using Kiva4

Abstract: The objective of this study was to investigate performance characteristics of a spark ignition engine, particularly, the correlation between performance, exhaust gas temperature and speed, using Kiva4. Test data to validate kiva4 simulation results were conducted on a 3-cylinder, four-stroke Volkswagen (VW) Polo 6 TSI 1.2 gasoline engine. Three different tests were, therefore, carried out. In one set, variations in exhaust gas temperature were studied by varying the engine load, while keeping the engine speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…As the study of changes occurring in a gaseous system with varying conditions is a subject of interest, various attempts in this context are being made these days. J. Lungu et al [5] have studied a correlation between performance, engine speed, load and exhaust gas temperature of a spark ignition gasoline engine by performing experiments and by numerical simulations using an advanced computational fluid dynamics modeling code, Kiva4. It is shown that how the performance of an engine is affected by the exhaust gas temperature.…”
Section: Introduction and A Brief Review Of The Field And Related Areasmentioning
confidence: 99%
“…As the study of changes occurring in a gaseous system with varying conditions is a subject of interest, various attempts in this context are being made these days. J. Lungu et al [5] have studied a correlation between performance, engine speed, load and exhaust gas temperature of a spark ignition gasoline engine by performing experiments and by numerical simulations using an advanced computational fluid dynamics modeling code, Kiva4. It is shown that how the performance of an engine is affected by the exhaust gas temperature.…”
Section: Introduction and A Brief Review Of The Field And Related Areasmentioning
confidence: 99%